PERUBAHAN MASYARAKAT MELAYU DI KOTA MEDAN: SUATU KAJIAN TENTANG TRADISI MEMBANGUN RUMAH TINGGAL - Azmi Azmi; Adek Cerah Kurnia Azis (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2021)
This research was conducted to prove the changes in Malay society by studying the tradition of building houses, in the city of Medan, North Sumatra. The study used a qualitative descriptive method with an ethnomethodology and ethnoscience design, using 10 research subjects on stilt houses. This research instrument uses documentation and interview techniques which comprehensively want to see the cultural phenomenon of the Malay community in the city of Medan, in relation to the tradition of building houses. The results of the data analysis technique used by the Miles and Huberman model show that the change in the shape of the traditional house is caused by the Malay traditional factor which provides openness and flexibility. The changes in the Malay community in the city of Medan have caused the elements of traditional culture to be lost, but it is better that there are new cultural aspects that arise. The phenomenon of cultural transformation of the Malay community so far has taken place according to a flexible framework of customary rules, in responding to changing times it is still acceptable. The implication of the research results is that in some cases there is a tendency that the houses referred to are types of houses on stilts typology I and II, as “traditional identities.” As for residential buildings, “modern identity” is a typology or style III stilt house, which is more varied, monumental and formal. Furthermore, in some buildings, it can be seen that traditional building structures are not integrated with modern structures. Impressed with the value of decorative or ornamental carvings tend to change a lot, especially those of sacred, mystical and religious value. In essence, the Malay tradition of traditional Malay formulates that there are: